Syntactic Patterns in Croatian WordNet - Šojat, Krešimir (Array, 2010)
The paper presents the detection of syntactic patterns in the Croatian WordNet synset definitions. The detection was performed in order to create unambiguous and consistent synset definitions in the future development of the Croatian WordNet. The rules are implemented in form of finite-state transducers and tested on already existing version of the Croatian WordNet. Results are presented using standard evaluation measures.